Exocrine-Endocrine Crosstalk: The Influence of Pancreatic Cellular Communications on Organ Growth, Function and Disease - Overton, Danielle L.; Mastracci, Teresa L. (Frontiers in Endocrinology, 2022)
Diabetes mellitus, a disease that affects nearly 463 million people worldwide, is characterized by the death or dysfunction of insulin-producing beta cells of the pancreas. The beta cells are found within the islets of Langerhans, which are composed of multiple hormone-producing endocrine cells including the alpha (glucagon), delta (somatostatin), PP (pancreatic polypeptide), and epsilon (ghrelin) cells. There is direct evidence that physical and paracrine interactions between the cells in the islet facilitate and support beta cell function. However, communication between endocrine and exocrine cells in the pancreas may also directly impact beta cell growth and function. Herein we review literature that contributes to the view that “crosstalk” between neighboring cells within the pancreas influences beta cell growth and function and the maintenance of beta cell health.